2012
DOI: 10.1167/12.8.5
|View full text |Cite
|
Sign up to set email alerts
|

Auditory transients do not affect visual sensitivity in discriminating between objective streaming and bouncing events

Abstract: With few exceptions, the sound-induced bias toward bouncing characteristic of the stream/bounce effect has been demonstrated via subjective responses, leaving open the question whether perceptual factors, decisional factors, or some combination of the two underlie the illusion. We addressed this issue directly, using a novel stimulus and signal detection theory to independently characterize observers' sensitivity (d') and criterion (c) when discriminating between objective streaming and bouncing events in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 27 publications
2
28
1
Order By: Relevance
“…This analysis opens up another possible line of investigation in which transients such as tones or visual flashes at or near the point of coincidence, which would suggest bouncing, are pitted against perceptual grouping cues, such as proximity, size, shape, color, and smooth continuation, which could be rendered consistent with streaming. A variety of cue combinations could be investigated to determine the relative strength of organizing cues in a similar approach to Grove and Sakurai (2009), who showed that auditory-induced bouncing persisted even when the trajectories of the individual disks were spatially displaced, tipping the probability of the resolution towards streaming (see also Grove, Ashton, Kawachi, & Sakurai, 2012 for a similar effect when the targets were rendered distinguishable via texture density differences).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis opens up another possible line of investigation in which transients such as tones or visual flashes at or near the point of coincidence, which would suggest bouncing, are pitted against perceptual grouping cues, such as proximity, size, shape, color, and smooth continuation, which could be rendered consistent with streaming. A variety of cue combinations could be investigated to determine the relative strength of organizing cues in a similar approach to Grove and Sakurai (2009), who showed that auditory-induced bouncing persisted even when the trajectories of the individual disks were spatially displaced, tipping the probability of the resolution towards streaming (see also Grove, Ashton, Kawachi, & Sakurai, 2012 for a similar effect when the targets were rendered distinguishable via texture density differences).…”
Section: Discussionmentioning
confidence: 99%
“…My colleagues and I have made a similar point with respect to perceptual and response-based biases analyzed using signal detection theory (Witt, Taylor, Sugovic, & Wixted, 2015). Some researchers have claimed, solely on the basis of an effect on the bias measure c, that the effect is due to response-based bias and is not perceptual (e.g., Choe, Welch, Gilford, & Juola, 1975;Grove, Ashton, Kawachi, & Sakurai, 2012). In contrast, we used simulations of the Müller-Lyer illusion to show that both a perceptual bias and a response-based bias can produce the exact same pattern in the measure c. In other words, when the Müller-Lyer illusion is modeled as a perceptual bias in which lines with tails oriented inward appear shorter than lines with tails outward (i.e., the classic interpretation of this bias), 1002 Psychon Bull Rev (2017) 24:999-1021 signal detection theory analyses showed a large effect on c but no effect on d'.…”
mentioning
confidence: 87%
“…Thus, it can reflect the subject's decision criterion. In fact, c is often used synonymously with "criterion" and is therefore commonly thought to reveal cognitive contributions to the decision-making process and involve areas downstream of sensory cortex (McDonald et al, 2000;Grove et al, 2012;Jones et al, 2015;de Gee et al, 2017;Crapse et al, 2018;Luo and Maunsell, 2018;van Vugt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%